Penerapan SEO di Jurnal Garut dalam Meningkatkan Daya Saing - Putera, Muhammad Rezaldy; Rosyidi, Imron; Muslim, Acep (Annaba: Jurnal Ilmu Jurnalistik, 2020)
This study aims to determine the implementation of on page SEO, off page SEO and the competitiveness of Garut Journal in search engines. The research method used is descriptive where this method is used to provide an overview of the phenomenon of using SEO in online media today. The results of this study found that Jurnal Garut implemented a number of SEO elements on the page such as keyword placement, minimum paragraphs, and internal links. Jurnal Garut also carries out off-page SEO activities by embedding links on social media and getting a number of natural backlinks. Competition, traffic and income are the main factors for Journal Garut in applying SEO techniques. As for increasing competitiveness in search engines, Jurnal Garut uses the help of Google Analytics and Google Trends applications to find the right keywords, and increase the quantity of writing. In search engines, Jurnal Garut is able to compete with other media.